Circulating plasma IL-13 and periostin are dysregulated type 2 inflammatory biomarkers in prurigo nodularis: A cluster analysis - Parthasarathy, Varsha; Cravero, Karen; Deng, Junwen; Sun, Zhe; Engle, Sarah M.; Auxier, Autum N.; Hahn, Nathan; Sims, Jonathan T.; Okragly, Angela J.; Alphonse, Martin P.; Kwatra, Shawn G. (Frontiers in Medicine, 2022)
Importance: Prurigo nodularis (PN) is a chronic heterogeneous inflammatory skin disease. Objective: To elucidate which components of type 2 inflammation are dysregulated systemically in PN. Design: Whole blood was obtained from PN patients with uncontrolled disease and control patients without pruritus. Plasma was assayed for IL-4, IL-5, IL-13, IgE, and periostin. ANOVA was utilized to compare PN and control patients and multiple-hypothesis adjusted p-value was calculated with the significance threshold at 0.05. Clustering was performed using K-means clustering. Participants: PN patients (n=29) and controls (n=18) from Johns Hopkins Dermatology had similar age sex, and race distributions. Results: Single-plex assays of the biomarkers demonstrated elevated circulating plasma IL-13 (0.13 vs. 0.006 pg/mL, p=0.0008) and periostin (80.3 vs. 60.2 ng/mL, p=0.012) in PN compared to controls. IL-4 (0.11 vs. 0.02 pg/mL, p=0.30) and IL-5 (0.75 vs. 0.40 pg/mL, p=0.10) were not significantly elevated, while IgE approached significance (1202.0 vs. 432.7 ng/mL, p=0.08). Clustering of PN and control patients together revealed two clusters. Cluster 1 (n=36) consisted of 18 PN patients and 18 controls. Cluster 2 (n=11) consisted entirely of PN patients (p<0.01). Cluster 2 had higher levels of IL-13 (0.33 vs. 0.008 pg/mL, p=0.0001) and IL-5 (1.22 vs. 0.43 pg/mL, p=0.03) compared to cluster 1. Conclusions and Relevance: This study demonstrates elevation of IL-13 and periostin in the blood of PN patients, with distinct clusters with varying degrees of type 2 inflammation. Given this heterogeneity, future precision medicine approaches should be explored in the management of PN.